2016
DOI: 10.4068/cmj.2016.52.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Association ofAPOEGenotype with Bone Mineral Density in Men and Women: The Dong-gu and Namwon Studies

Abstract: Many studies have investigated relationships between APOE genotype and bone mineral density (BMD). However, the results of these studies have been inconsistent. Few studies have been carried out in Asian populations. We studied the relationship of the APOE gene polymorphism and BMD in two large population-based studies. The datasets included the Dong-gu Study (3575 men and 5335 women) and the Namwon Study (2310 men, 3512 women). Lumbar spine and femoral neck BMD were measured by dual-energy X-ray absorptiometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In the present study we found the APOE genotypes E2E2, E2E3, E3E3, E3E4 and E4E4 with frequency of 0.8, 6, 69, 21 & 3% respectively in cases and 0, 8, 73, 15 & 3% respectively in controls; and the allele frequency of E2, E3 and E4 was found to be 3.6, 82.5 and 13.9% respectively in cases and 4, 85 and 10.9% respectively in controls. This genotype frequency is in accordance with the previous reports (Kim et al, 2016). Though we found high frequency of E4 allele in cases (13.9%) when compared to control (10.9%), the difference was not statistically significant.…”
Section: Discussion:-supporting
confidence: 92%
See 1 more Smart Citation
“…In the present study we found the APOE genotypes E2E2, E2E3, E3E3, E3E4 and E4E4 with frequency of 0.8, 6, 69, 21 & 3% respectively in cases and 0, 8, 73, 15 & 3% respectively in controls; and the allele frequency of E2, E3 and E4 was found to be 3.6, 82.5 and 13.9% respectively in cases and 4, 85 and 10.9% respectively in controls. This genotype frequency is in accordance with the previous reports (Kim et al, 2016). Though we found high frequency of E4 allele in cases (13.9%) when compared to control (10.9%), the difference was not statistically significant.…”
Section: Discussion:-supporting
confidence: 92%
“…Simultaneously, there have been reports showing no association of E4 allele with osteoporosis since its first report by Booth et al, which included 888 subjects from Framingham heart study (Booth et al, 2000). The recent study that claims to have used largest sample size of 14,732 subjects, also could not find the association of APOE4 with osteoporosis (Kim et al, 2016).…”
Section: Discussion:-mentioning
confidence: 99%
“…A Japanese study in older women also reported a decrease in spine BMD [ 8 ]. A study performed in community-dwelling women who were 45 years of age and older and living in a South-Western Korean province reported no difference in BMDs based on the ε4 allele at the spine and femoral neck [ 17 ]. The current study was conducted at a single tertiary hospital in Seoul, Korea, and included younger postmenopausal women with menopausal syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…[204][205][206][207] Several large studies that included males and females did not find an association of APOE genotype with bone mineral density (BMD). [208][209][210][211][212] However, targeted studies of postmenopausal woman find APOE4 carriers have lower BMD [213][214][215][216][217] or higher hip fracture risk, 218 although there have been null findings. 219 A meta-analysis found APOE4 to be associated with significantly lower BMD in trochanteric and lumbar spine, predominantly in females.…”
Section: Apoe Menopause and Htmentioning
confidence: 99%
“…In particular, significant bone loss occurs at the onset of menopause and diminishes in later life with HT 204–207 . Several large studies that included males and females did not find an association of APOE genotype with bone mineral density (BMD) 208–212 . However, targeted studies of postmenopausal woman find APOE4 carriers have lower BMD 213–217 or higher hip fracture risk, 218 although there have been null findings 219 .…”
Section: Estrogen and Apoe Interactions Beyond Cnsmentioning
confidence: 99%